Autism and COVID-19 : strategies for supporters to help autistics and their families - Bennett, Matthew; Goodall, Emma (Emerald Publishing Limited, 2022)
The COVID-19 pandemic has had a profound and potentially ever-lasting impact on our economy, society, and the way that we live. In response to this pandemic there has been a plethora of research published about COVID-19. However, within this fast-growing body of literature there are only scant references made to the impact that this pandemic has had on autistics, their families, and the healthcare professionals who support autistics. Autism and COVID-19 is a concise summary of the research, bridging the gaps in our knowledge about autism and the COVID-19 pandemic. Bennett and Goodall address vaccine hesitancy among autistics and parents raising autistic children, the experiences of autistics living with COVID-19 disease and parenting an autistic child during the COVID-19 pandemic, synthesising the data about the COVID-19 pandemic from the perspective of autistic, their families, and those that provide autistics with medical assistance. Autism and COVID-19 both reviews the existing literature and presents new findings from a survey distributed to autistics and parents of autistics during the pandemic, all of which offer a unique and timely contribution to researchers, academics, practitioners, and those working with autistics and their families.
Keywords: Autistic people -- Care.; COVID-19 Pandemic, 2020 -- Influence.; Parents of autistic children -- Care.; Social Science / People with Disabilities.; Autism & Aspergers Syndrome.; elektronické knihy; electronic books